UPAYA MENINGKATKAN KEMAMPUAN MOTORIK KASAR MELALUI PERMAINAN TRADISIONAL PADA ANAK KELOMPOK B”RA AN-NUR TUNJUNGTIRTO KECAMATAN SINGOSARI KABUPATEN MALANG - Maulidah Rahmawati; Mohammad Afifulloh; Yorita Febry Lismanda (UNISMA, 2019)
This research was focusing on the development on gross motor of children group B RA AN-NUR Tunjungtirto, Singosari due to the lack of physical stimulation of the child’s gross motor. Fine motor activities are given more than the gross motor. Teachers only use books when stimulating child’s gross motor, and found 10 out of 16 children have difficulty walking on a level board, jumping on one foot, and throwing the ball with both hands. The type of research design used in this research was Classroom Action Research (CAR) with the subject of research were 16 children group B RA AN-NUR Tunjungtirto, Singosari school year 2018/2019. The data in this research was obtained through interviews, observation, and documentations. This research was carried out with two cycles, first cycle and second cycle, and each of the cycle contains two meetings. The result of the research indicates that using traditional game, Egrang Batok, can enhance the child’s gross motor development assessments of aspect 1, aspect 2, and aspect 3. As the result of increases can be seen at the following exposure, in the pre-cycle’s action has been found 0% with the explanation that no child has met the predetermined standard of success. At the first cycle in the first meeting increased and reached 3 children or 18,75% of 16 children. The second meeting of the first cycle reached 9 children or was 56,25% of 16 children. Also an increase in second cycle in the first meeting reached 11 children or amounted to 68,75% of 16 children. As well as a second meeting of the second cycle reached 15 children or 93,75% of 16 children. This shows that using traditional Egrang Batok game can increase the child’s gross motor skills from cycle to cycle in the children group B RA AN-NUR Tunjungtirto, Singosari. This research was suspended on second cycle for fulfilling the expected targets of 80% and learning indicators.